KREATIVITAS DAN HASIL BELAJAR: (Studi tentang Mahasiswa Pendidikan Matematika di Universitas Balikpapan) - Besse Intan Permatasari (Prodi Pendidikan Matematika, FKIP, Universitas Balikpapan, 2018)
This study aims to determine whether there is an influence of creativity on mathematics learning outcomes of students of Mathematics Education in University of Balikpapan Study Program on Linear Algebra Courses. The approach used is a quantitative approach with ex post facto research type. The population of this research is all students of Mathematics Education Study Program Linear Algebra Course in the School Year 2017/2018, which are 49 students. Samples were chosen randomly are 25 students. The results showed that there is a positive and significant effect on student learning outcomes in Linear Algebra Subject